Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Discover in-depth solutions to your questions from a wide range of experts on our user-friendly Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Let's analyze each pair of functions to determine for which pair the composition [tex]\((f \circ g)(x) = x\)[/tex] and [tex]\((g \circ f)(x) = x\)[/tex] holds true.
### Pair 1: [tex]\( f(x) = x^2 \)[/tex] and [tex]\( g(x) = \frac{1}{x} \)[/tex]
1. Compute [tex]\( (f \circ g)(x) \)[/tex]:
[tex]\[ f(g(x)) = f\left(\frac{1}{x}\right) = \left(\frac{1}{x}\right)^2 = \frac{1}{x^2} \][/tex]
2. Compute [tex]\( (g \circ f)(x) \)[/tex]:
[tex]\[ g(f(x)) = g(x^2) = \frac{1}{x^2} \][/tex]
For these functions, [tex]\((f \circ g)(x) \neq x\)[/tex] and [tex]\((g \circ f)(x) \neq x\)[/tex].
### Pair 2: [tex]\( f(x) = \frac{2}{x} \)[/tex] and [tex]\( g(x) = \frac{2}{x} \)[/tex]
1. Compute [tex]\( (f \circ g)(x) \)[/tex]:
[tex]\[ f(g(x)) = f\left(\frac{2}{x}\right) = \frac{2}{\frac{2}{x}} = x \][/tex]
2. Compute [tex]\( (g \circ f)(x) \)[/tex]:
[tex]\[ g(f(x)) = g\left(\frac{2}{x}\right) = \frac{2}{\frac{2}{x}} = x \][/tex]
For this pair, [tex]\((f \circ g)(x) = x\)[/tex] and [tex]\((g \circ f)(x) = x\)[/tex]. So, this pair satisfies the condition.
### Pair 3: [tex]\( f(x) = \frac{x-2}{3} \)[/tex] and [tex]\( g(x) = 2 - 3x \)[/tex]
1. Compute [tex]\( (f \circ g)(x) \)[/tex]:
[tex]\[ f(g(x)) = f(2 - 3x) = \frac{(2 - 3x) - 2}{3} = \frac{-3x}{3} = -x \][/tex]
2. Compute [tex]\( (g \circ f)(x) \)[/tex]:
[tex]\[ g(f(x)) = g\left(\frac{x-2}{3}\right) = 2 - 3 \left(\frac{x-2}{3}\right) = 2 - (x - 2) = 4 - x \][/tex]
For these functions, [tex]\((f \circ g)(x) \neq x\)[/tex] and [tex]\((g \circ f)(x) \neq x\)[/tex].
### Pair 4: [tex]\( f(x) = \frac{1}{2}x - 2 \)[/tex] and [tex]\( g(x) = \frac{1}{2}x + 2 \)[/tex]
1. Compute [tex]\( (f \circ g)(x) \)[/tex]:
[tex]\[ f(g(x)) = f\left(\frac{1}{2}x + 2\right) = \frac{1}{2}\left(\frac{1}{2}x + 2\right) - 2 = \frac{1}{4}x + 1 - 2 = \frac{1}{4}x - 1 \][/tex]
2. Compute [tex]\( (g \circ f)(x) \)[/tex]:
[tex]\[ g(f(x)) = g\left(\frac{1}{2}x - 2\right) = \frac{1}{2}\left(\frac{1}{2}x - 2\right) + 2 = \frac{1}{4}x - 1 + 2 = \frac{1}{4}x + 1 \][/tex]
For these functions, [tex]\((f \circ g)(x) \neq x\)[/tex] and [tex]\((g \circ f)(x) \neq x\)[/tex].
### Conclusion
The only pair of functions for which [tex]\((f \circ g)(x) = x\)[/tex] and [tex]\((g \circ f)(x) = x\)[/tex] is:
[tex]\[ f(x) = \frac{2}{x} \quad \text{and} \quad g(x) = \frac{2}{x} \][/tex]
So, the correct answer is the second pair.
### Pair 1: [tex]\( f(x) = x^2 \)[/tex] and [tex]\( g(x) = \frac{1}{x} \)[/tex]
1. Compute [tex]\( (f \circ g)(x) \)[/tex]:
[tex]\[ f(g(x)) = f\left(\frac{1}{x}\right) = \left(\frac{1}{x}\right)^2 = \frac{1}{x^2} \][/tex]
2. Compute [tex]\( (g \circ f)(x) \)[/tex]:
[tex]\[ g(f(x)) = g(x^2) = \frac{1}{x^2} \][/tex]
For these functions, [tex]\((f \circ g)(x) \neq x\)[/tex] and [tex]\((g \circ f)(x) \neq x\)[/tex].
### Pair 2: [tex]\( f(x) = \frac{2}{x} \)[/tex] and [tex]\( g(x) = \frac{2}{x} \)[/tex]
1. Compute [tex]\( (f \circ g)(x) \)[/tex]:
[tex]\[ f(g(x)) = f\left(\frac{2}{x}\right) = \frac{2}{\frac{2}{x}} = x \][/tex]
2. Compute [tex]\( (g \circ f)(x) \)[/tex]:
[tex]\[ g(f(x)) = g\left(\frac{2}{x}\right) = \frac{2}{\frac{2}{x}} = x \][/tex]
For this pair, [tex]\((f \circ g)(x) = x\)[/tex] and [tex]\((g \circ f)(x) = x\)[/tex]. So, this pair satisfies the condition.
### Pair 3: [tex]\( f(x) = \frac{x-2}{3} \)[/tex] and [tex]\( g(x) = 2 - 3x \)[/tex]
1. Compute [tex]\( (f \circ g)(x) \)[/tex]:
[tex]\[ f(g(x)) = f(2 - 3x) = \frac{(2 - 3x) - 2}{3} = \frac{-3x}{3} = -x \][/tex]
2. Compute [tex]\( (g \circ f)(x) \)[/tex]:
[tex]\[ g(f(x)) = g\left(\frac{x-2}{3}\right) = 2 - 3 \left(\frac{x-2}{3}\right) = 2 - (x - 2) = 4 - x \][/tex]
For these functions, [tex]\((f \circ g)(x) \neq x\)[/tex] and [tex]\((g \circ f)(x) \neq x\)[/tex].
### Pair 4: [tex]\( f(x) = \frac{1}{2}x - 2 \)[/tex] and [tex]\( g(x) = \frac{1}{2}x + 2 \)[/tex]
1. Compute [tex]\( (f \circ g)(x) \)[/tex]:
[tex]\[ f(g(x)) = f\left(\frac{1}{2}x + 2\right) = \frac{1}{2}\left(\frac{1}{2}x + 2\right) - 2 = \frac{1}{4}x + 1 - 2 = \frac{1}{4}x - 1 \][/tex]
2. Compute [tex]\( (g \circ f)(x) \)[/tex]:
[tex]\[ g(f(x)) = g\left(\frac{1}{2}x - 2\right) = \frac{1}{2}\left(\frac{1}{2}x - 2\right) + 2 = \frac{1}{4}x - 1 + 2 = \frac{1}{4}x + 1 \][/tex]
For these functions, [tex]\((f \circ g)(x) \neq x\)[/tex] and [tex]\((g \circ f)(x) \neq x\)[/tex].
### Conclusion
The only pair of functions for which [tex]\((f \circ g)(x) = x\)[/tex] and [tex]\((g \circ f)(x) = x\)[/tex] is:
[tex]\[ f(x) = \frac{2}{x} \quad \text{and} \quad g(x) = \frac{2}{x} \][/tex]
So, the correct answer is the second pair.
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.